A facile and versatile route for preparation AgNp nanocomposite thin films via thiol-acrylate photopolymerization: Determination of antibacterial activity - Adibelli, Melisa; Ozcelik, Elif; Batibay, Gonul S.; Arasoglu, Tulin Ozbek; Arsu, Nergis (ELSEVIER SCIENCE SA, 2020)
Size, shape and distribution-controlled silver nanoparticles (AgNps) were produced by a rapid and efficient method either in solvent or in polymer matrix by which the silver ion is reduced and a polymer matrix is simultaneously generated in the presence of various photoinitiators by the means of UV light. 2-Mercaptothioxanthone (TX-SH), Thioxanthone (TX) and TX+ Thiophenol were used as photoinitiator systems for the polymerization of PEGMEA/PEGDA monomer mixture in the presence of AgNO3 salt. As a summary of results, it is important to note that the size and distribution of Nps depend on the photoreducing species. Therefore TX-SH, due to thiol functionality in its structure, helped production of he 7-40 nm size and distribution-controlled AgNps in polymer matrix. In-situ prepared AgNps/Polymer nanocoatings exhibited a reflected silver mirror view as a result of aggregation depending on the irradiation time. Antibacterial efficiency and susceptibility of AgNps containing nanocomposite films were examined for t E. coli, P. aeruginosa, S. aureus and B. cereus. Obtained antimicrobial results show that photochemically prepared nanocomposites considerably increase the antimicrobial activity on Gram negative bacteria compared to Gram positive bacteria.
Keywords: Silver nanoparticles; Nanocomposites; Antibacterial activity; Photopolymerization; Functional coatings; FREE-RADICAL POLYMERIZATION; GOLD NANOPARTICLES; PHOTOCHEMICAL-SYNTHESIS; ELECTRON-TRANSFER; PHOTOINITIATOR; NANOCRYSTALLITES; MATRIX; LASER; Chemistry; Materials Science